Biofluid‐Triggered Burst Release from an Adaptive Covalently Assembled Dipeptide Nanocontainer for Emergency Treatment. Issue 7 (8th February 2017) - Fei, Jinbo; Zhang, He; Wang, Anhe; Qin, Chenchen; Xue, Huimin; Li, Junbai
Abstract : The construction of quickly dissociating containers holding bioactive components that meet the extreme requirements of emergency treatment is highly desirable but remains a great challenge. Here the use of small‐molecule‐induced dynamic covalent assembly is reported for simple and tunable fabrication of a biocompatible diphenylalanine‐based nanocontainer toward rapidly responsive cargo delivery. The assembled nanocontainer can adaptively encapsulate various charged or neutral molecules. Upon biofluid trigger, the encapsulated molecules and bioactive proteins are released in a burst (within 5 s) from the nanocontainer due to highly sensitive deprotonation‐mediated disruption of hydrogen bonding. This highlighted feature allows the nanocontainer as an excellent "fast dissolving" delivery vehicle available in spray dosage form for medical emergencies, as demonstrated by in vivo application for massive hemorrhage. Abstract : A biocompatible and adaptive dipeptide‐based nanocontainer is fabricated in a tunable manner through facile small‐molecule‐induced dynamic covalent assembly. Upon biofluid trigger, bioactive proteins encapsulated by the assembled nanocontainer can be released in a burst (within 5 s) without residuals. This highlighted feature permits the nanocontainer as a good "fast dissolving" delivery vehicle toward medical emergencies.